Implementation of Human Resources Management at PT Bangun Bangsa: Challenges and Development Strategies - Sri Lestari (PT. Putra Jawa Mulya ( Putra Jawa Publisher ), 2024)
This research aims to analyze the implementation of human resource management (HRDM) at PT Bangun Bangsa, with a focus on the challenges faced and the development strategies implemented. The research uses a qualitative approach with data collection methods through interviews, observation, and document analysis. The research results show that PT Bangun Bangsa faces various challenges in managing human resources, including difficulties in recruiting quality workers, the need for more targeted training programs, and challenges in retaining employees. The strategies implemented by the company include strengthening the selection and recruitment process, developing sustainable training programs, implementing a more transparent performance management system, and increasing employee involvement through engagement and retention programs. This research provides insight into the important role of HRM in improving organizational performance and offers recommendations for improving HRM practices at PT Bangun Bangsa.